Vaccination of adult patients living with chronic kidney disease against SARS-CoV-2: a position statement by the South African Nephrology Society - Davies, Malcolm; van Hougenhouck-Tulleken, Wesley; Diana, Nina E; Chothia, M Yazied; Nel, Jeremy; Wearne, Nicola; Wadee, Shoyab; Hariparshad, Sudesh (African Journal of Nephrology, 2021)
Safe and effective vaccination of patients living with chronic kidney disease requires an understanding of the unique immunological milieu of this population and of their potential for disease-specific side effects. This Position Statement, issued on behalf of the South African Nephrology Society, provides recommendations for local policy development and for individual practice administration and monitoring of SARS-CoV-2 vaccinations in patients living with chronic kidney disease.